Prematurity, chorioamnionitis, and the development of recurrent wheezing: A prospective birth cohort study - Kumar, Rajesh; Yu, Yunxian; Story, Rachel E.; Pongracic, Jacqueline A.; Gupta, Ruchi; Pearson, Colleen; Ortiz, Kathryn; Bauchner, Howard C.; Wang, Xiaobin (Journal of allergy and clinical immunology, 2008)
Prematurity (<37 weeks) has been inconsistently associated with asthma and wheezing. Chorioamnionitis may promote both prematurity and inflammatory pathways in infants' airways. To investigate the relationship of prematurity and chorioamnionitis with the development of early childhood recurrent wheezing. The Boston Birth Cohort (n = 1096) were followed prospectively from birth to a mean age of 2.2 ± 2 years. Perinatal and postnatal clinical data and placental pathology were collected. The primary outcome was recurrent wheezing (≥2 physician documented episodes). Secondary outcomes included physician-diagnosed asthma, food allergy, and eczema. Preterm children were grouped by gestational age into moderately (33-36.9 weeks) and very preterm (<33 weeks) with and without chorioamnionitis, and compared with term children without chorioamnionitis (reference group). Chorioamnionitis was diagnosed either by intrapartum fever or by placental histology findings. Logistic regression models were performed to investigate the independent and joint associations of degree of prematurity and chorioamnionitis. Prematurity was associated with recurrent wheezing (odds ratio [OR], 1.7; 95% CI, 1.2-2.6). However, when subjects were grouped by degree of prematurity with or without chorioamnionitis, the highest risk of wheezing (OR, 4.0; 95% CI, 2.0-8.0) and physician-diagnosed asthma (OR, 4.4; 95% CI, 2.2-8.7) was present in the very preterm children with chorioamnionitis. The effect on both wheezing (OR, 5.4; 95% CI, 2.4-12.0) and asthma (OR, 5.2; 95% CI, 2.3-11.9) was greater in African Americans. Neither prematurity nor chorioamnionitis was associated with food allergy or eczema. We found a strong joint effect of prematurity and chorioamnionitis on early childhood wheezing. This effect was stronger in African American subjects.